PEMIKIRAN AMIN ABDULLAH - Uqbatul Khair Rambe (UIN Sumatera Utara, 2019)
Amin Abdullah is a productive thinker in the arena of Indonesian Muslim scholars. Amin is not only able to synthesize among many conflicting arguments, but also more than that He is able to produce an intelligent and accommodating concept, so that a concept can be an answer to the problems raised. Amin Abdullah is an Islamic thinker in Indonesia. At first he was a santri whose life was full of conservative things. Even the pesantren learning system in Indonesia today is learning that emphasizes more on the rote system and not on the system of thought. But an Amin Abdullah has now become a thinker, even now many people call him an Indonesian philosopher. Amin Abdulah's thought is known for being so contemporary, because when viewed from various scientific writings he presents many present-day problems. Current issues that are often raised are problems in the post modern era, the dynamics of cultural Islam, and mapping of contemporary Islamic discourse.